Pengaruh Pola Rekrutmen Dan Disiplin Kerja Kepala Sekolah Terhadap Kinerja Kepala Sekolah Smp Di Kabupaten Lombok Tengah - Zainuri, Lalu (Jurnal Ilmiah Mandala Education (JIME), 2022)
The purpose of this study was to determine the effect of recruitment patterns and work discipline on the performance of junior high school principals in Lombok Regency in Central Lombok Regency. This research is an explanatory research. The research design chosen was a non-experimental design. The population in this study were 92 state junior high schools in Central Lombok Regency. Samples were taken using a disproportionate stratified random sampling technique (4 schools with a recruitment pattern of 1, 36 with a pattern of 2, and 4 schools with a pattern of 3). Recruitment pattern data were collected using documentation techniques, principal discipline data and principal performance were collected using a questionnaire technique using a Likert scale. The data were analyzed by descriptive statistics and inferential statistics to test the hypothesis. Hypothesis testing was carried out through a univariate general linear model (GLM) procedure using SPSS 20.0 at a significance level of 5%. The research results show; (1) the principal's recruitment pattern has a significant effect on the principal's performance (F = 13,471, p<0,05), (2) the principal's discipline has a significant effect on the principal's performance (F = 4,999, p<0,05), and (3) The pattern of recruitment and discipline of school principals together has a significant effect on the performance of junior high